Fabrication of Flexible Graphite Film Using a Mechanical Method and Its Application in Tio2/Graphite Solar Cell as a Flexible Counter Electrode. (August 2019) - Rahman, Dui Yanto; Utami, Fisca Dian; Margaretta, Desyana Olenka; Sustini, Euis; Abdullah, Mikrajuddin
Abstract: We have successfully fabricated solar cell using flexible counter electrode of graphite powder. TiO2 / graphite suspension was simply poured onto heated Fluorine Tin Oxide (FTO) substrate and kept heated at 200°C for 2 hours. PVA.LiOH polymer electrolyte was employed as a positive charge transfer medium. The counter electrode was made of graphite powder which is manually deposited on transparent plastic using tube-shaped metal which its surface covered with tissue of 2 mm thick. Graphite powder was deposited by straight motion of 20 movements for one coating or one layer. The same activity was repeated on the stacked film to increase the conductivity of the film. Resistivity and transmittance measurement of the film was performed by four-point probe method and UV-Vis equipment respectively. The film thickness and 2-D porosity were measured using an electronic microscope and ImageJ software orderly. The film resistivity and transmittance gradually decreased with the increase of coating number and reached the resistivity of 0.35 Ω.cm and transmittance of 5% for 40 times of coating. At the same time, the film thickness was saturated at the 30 times coating and reached the thickness of 9.4 μm. The film 2-D porosity which indicated how well the surface of the film covered the graphite also decreased to reach the film porosity of 18%. The most conductive film (40 times coating) was used as a flexible counter electrode in TiO2 /graphite solar cell. The efficiency of this structure was 0.4 %, a reasonable efficiency achievement for a cheap material and easy method used.